Hubungan Lama Penggunaan KB Suntik 3 Bulan dengan Gangguan Pola Menstruasi di TPMB Fadlilah Nury Kecamatan Poncokusumo - Wijayati, Nurul Ani; Alfitri, Rosyidah; Wijayanti, Tut Rayani Aksohini (Fakultas Ilmu Kesehatan, 2025)
Three month injectable contraception is one way to prevent pregnancy with injections containing hormones. One of the side effects of this contraceptive method is disruption of menstrual patterns with long-term use. The aim of this study was to determine the relationship between the duration of using contraceptive injections for 3 months and menstrual pattern disorders in women of childbearing age. This research was conducted from July 1 to September 29 2024 at TPMB Fadilah Nury, Poncokusumo District. This research method is an analytical survey with a cross sectional approach. The sample in this study was 42 respondents who met the inclusion and exclusion criteria. Independent variable: Length of use of injectable birth control 3 months. Dependent variable Menstrual Pattern Disorders. The sampling method is using total sampling technique. Data collection techniques use primary data and questionnaires. Based on the research results, it was found that from 42 respondents (100%) using 3-month contraceptive injections for a period of >2 years, 38 respondents (90.5%) experienced menstrual pattern disorders and <2 years, 4 respondents (9.5%) did not experience any disorders. menstrual pattern. Data analysis used Chi-square Î±<0.05. The results of the Chi-square test are p value = 0.006. The conclusion of this research is that there is a significant relationship between the duration of using injectable contraceptives for 3 months and menstrual pattern disorders in TPMB Fadlilah Nury, Poncokusumo District.